Encrypted data transmission through typical HTTP channel for embedded devive server - 273791 Lee, Eugene Kok Chai; Kamal Khalil; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2007